Efeito das cargas de treinamento sobre parâmetros fisiológicos de futebolistas - Campos, Eduardo Zapaterra [UNESP]; Milioni, Fabio [UNESP]; Carvalho Zanuto, Everton Alex [UNESP]; Almeida, Pablo Barreto [UNESP]; Gobbi, Ronaldo Bucken [UNESP]; Andrade, Vitor Luiz de [UNESP]; Balikian Junior, Pedro [UNESP]; Papoti, Marcelo [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2013)
The aim of this study was to investigate the effects of three weeks of training with intensity monitored on the aerobic capacity of professional soccer players. Fourteen players, members of a first division Brazilian Championship team in 2010, aged 22.78 +/- 3.06 years were evaluated pre and post three weeks of training. The anaerobic threshold intensity LAn was determined by bi-segmented method, for this four submaximal efforts of 800 meters with intensities 10, 12, 14 and 16 km/h were applied. Thirty three training sessions were quantified in zones according to heart rate related to the LAn (FCLAn): Z1 - 10% below, Z2 - 90-100% and Z3 - above the FCLAn. During training participants remained 31.17 +/- 14.86%, 42.96% and 25.87 +/- 14.90 +/- 16.67% in Z1, Z2, and Z3 respectively. There were no significant differences in the LAn (pre = 13,29 +/- 0,71 km.h(-1); post = 12,85 +/- 0,90 km.h(-1)), perceived exertion (pre = 11,53 +/- 1,45 u.a; post = 11,23 +/- 1,53 u.a) and FCLAn (pre = 166,64 +/- 10,69 bpm; post = 174,50 +/- 10,89 bpm) between conditions before and after training, indicating that three weeks of training are insufficient to generate positive changes in soccer players LAn.

O objetivo desse estudo foi verificar os efeitos de três semanas de treinamentos com intensidades monitoradas sobre a capacidade aeróbia de futebolistas profissionais. Quatorze futebolistas integrantes de equipe da primeira divisão do Campeonato Brasileiro de 2010, foram avaliados pré e pós três semanas de treinamento. O limiar anaeróbio (LAn) foi determinado pelo método bi-segmentado, para isso quatro esforços submáximos de 800 metros com intensidades de 10, 12, 14 e 16 km/h foram aplicados. Trinta três sessões de treinamentos foram quantificadas em zonas de acordo com frequência cardíaca referente ao LAn (FCLAn): Z1 – 10% abaixo, Z2 – 90-100% e Z3 – acima da FCLAn. Durante os treinamentos os jogadores permaneceram 31,17±14,86%, 42,96±14,90% e 25,87±16,67% em Z1, Z2 e Z3, respectivamente. Não foram encontradas diferenças significativas no LAn (pré = 13,29 ± 0,71 km∙h-1 ; pós=12,85 ± 0,90 km∙h-1 ), percepção subjetiva de esforço correspondente ao LAn (pré = 11,53 ± 1,45 u.a; pós=11,23 ± 1,53 u.a) e FCLAn (pré = 166,64 ± 10,69 bpm; pós = 174,50 ± 10,89 bpm), indicando que três semanas de treinamento são insuficiente para gerar adaptações positivas no LAn de futebolistas.
Effect of training loads on physiological parameters of soccer players
Keywords: Anaerobic Threshold; Training; Soccer